Best Answer

If you meant 2x+3=4x²

x=(1±√(13))/4

x1≈1.151387818866

x2≈-0.651387818866

Q: 2x plus 3 equals 4x2

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2x + 3)(2x + 3)

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x2 plus 3=11

I assume you mean factors for 4x2+10x+6.(2x+3)(2x+2).

No, it has factors... 4x2 + 8x -21 = (2x+7)(2x-3)

Related questions

(2x + 3)(2x + 3)

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).

4x2 - 2x - 3 = 0 (2x + 1)(2x - 3) = 0 x = -(1/2) or (3/2)

(2x + 3)(2x - 1)

4x2 plus 3=11

This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)

I assume you mean factors for 4x2+10x+6.(2x+3)(2x+2).

No, it has factors... 4x2 + 8x -21 = (2x+7)(2x-3)

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2

4x2-4x-3 = 0 (2x-3)(2x+1) = 0 x = 3/2 or x = -1/2